2014
DOI: 10.2147/jmdh.s66712
|View full text |Cite
|
Sign up to set email alerts
|

The difficulties of interprofessional teamwork in diabetes care: a questionnaire survey

Abstract: BackgroundDiabetes is a multifactorial disease and its nature means that interprofessional teamwork is essential for its treatment. However, in general, interprofessional teamwork has certain problems that impede its function. To clarify these problems in relation to diabetes care, a questionnaire survey was conducted.MethodsThe participants who were involved in diabetes-related educational seminars, and medical personnel who were engaged in diabetes care from the National Center for Global Health and Medicine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…[ 13 – 79 ] Forty-five studies (Supplementary Table S1) came from 25 developed countries which reported IPE programs. [ 13 58 ] Supplementary Table S2, summarized the 20 [ 59 – 79 ] studies that conducted the IPE program in 16 developing countries, and mostly from West and East Asia. Few studies were available from Africa, and the Latin America and Caribbean region.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 13 – 79 ] Forty-five studies (Supplementary Table S1) came from 25 developed countries which reported IPE programs. [ 13 58 ] Supplementary Table S2, summarized the 20 [ 59 – 79 ] studies that conducted the IPE program in 16 developing countries, and mostly from West and East Asia. Few studies were available from Africa, and the Latin America and Caribbean region.…”
Section: Resultsmentioning
confidence: 99%
“…Based on all of the studies that we reviewed, we found that the university is the most common academic institution in IPE programs, except 1 IPE program which is conducted by the National Center for Global Health and Medicine in Japan. [ 58 ] However, the global movement of IPE initiatives and programs are unique for each university in developed and developing countries. As early as 1960, universities in Canada, the United States, the United Kingdom (UK), and Australia initiated IPE programs, whereas most universities in developing countries introduced IPE programs more recently.…”
Section: Resultsmentioning
confidence: 99%
“…Certified diabetes educator of Japan is a qualification awarded by the Japanese Certification Board for Diabetes Educators, to a nurse, dietitian, pharmacist, clinical laboratory technician, or physical therapist possessing wide specialist knowledge of diabetes, since 2000. 25,26 In addition, CDEs who play an active role in local areas are called local certified diabetes educators. Local certified diabetes educators are trained in a manner corresponding to the conditions of an individual local area.…”
Section: Discussionmentioning
confidence: 99%
“…Other factors such as insufficient “interprofessional teamwork” can be improved by continuous efforts by members. Interprofessional teamwork in diabetes care is extremely important (Dounis et al 2014 ; Ritholz et al 2011 ; Kishimoto and Noda 2014 ) and the successful use of CDEs on interprofessional teams suggests that expansion of the team approach might be effective in the provision of diabetes education services (Langelier et al 2010 ) and may raise CDE recognition levels. The factor of “limited personal ability” can be improved by individual effort and may lead to correcting mismatched allocations.…”
Section: Discussionmentioning
confidence: 99%